Astrocytic connexin 43 hemichannels activity under Alzheimer’s disease-like conditions: Regulation by adenosine A2A receptors - Domingues, Joana Sofia da Silva (2023)
Trabalho de Projeto do Mestrado em Engenharia Biomédica apresentado à Faculdade de Ciências e Tecnologia